2020
DOI: 10.1016/j.sjbs.2020.04.016
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Nigella sativa and Foeniculum vulgare seeds extracts on male mice exposed to carbendazim

Abstract: The increasing prevalence of environmental pollutants such as pesticides is a major global problem that affects living organisms. Exposure to environmental pollutants remains a major source of health risk throughout the world. The potential health benefits of various medicinal plants and natural products in relation to protect various diseases are currently receiving considerable attention. A current approach is to develop a new biological compound from natural products that inhibits pain. Ethnopharmacological… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 73 publications
4
9
0
Order By: Relevance
“…The restoration of functional integrity of pituitary–gonadal axis by dietary inclusion of NSS in MSG challenged rats is similar to that found in mice exposed to carbendazim 54 . This outcome may be attributed to the ability of NSS to increase the testicular steroidogenic enzymes activities 55 .…”
Section: Discussionsupporting
confidence: 76%
“…The restoration of functional integrity of pituitary–gonadal axis by dietary inclusion of NSS in MSG challenged rats is similar to that found in mice exposed to carbendazim 54 . This outcome may be attributed to the ability of NSS to increase the testicular steroidogenic enzymes activities 55 .…”
Section: Discussionsupporting
confidence: 76%
“…There was marked increase in testosterone level in A4 (treated only with Nigella sativa) as compared to groups A1, A2 and A3; this is in agreement with findings of [24,25], who reported that 2g of Nigella sativa capsules for three months significantly increases the testosterone and other reproductive hormones in humans [23,24] also support our findings.…”
Section: Discussionsupporting
confidence: 93%
“…This happens due to thymoquinone which has a key role in testicular protection due to its antioxidant, anti-apoptotic effects. It is also defensive against upper respiratory diseases, GIT disorders and skin problem [23,24,25]. This research work shows that nigella sativa has protective role against doxorubicin nephrotoxicity.…”
Section: Introductionmentioning
confidence: 80%
“…These results are in agreement with another study (2) who found that the separated doses of CBZ resulted in a significant increase in plasma urea and creatinine. Also, rats treated with CBZ alone resulted in significant increases in serum glucose (64%), urea (99%), and creatinine (52%) levels compare with the negative group (46). Treatment rats with ethanol extract of kumquat led to dramatically lower blood glucose, urea, and creatinine levels in rats.…”
Section: Parametermentioning
confidence: 93%